Estimation of Passenger Car Equivalents for Two-Lane and Turbo Roundabouts Using AIMSUN - Granà, Anna; Giuffrè, Tullio; Macioszek, Elżbieta; Acuto, Francesco (Frontiers in Built Environment, 2020)
The paper addresses issues related to Passenger Car Equivalents (PCEs) at roundabouts. Compared to other road units, the curvilinear elements of roundabout geometric design may impose greater constraints on vehicular trajectories and have a significant effect on the swept envelope of heavy vehicles. Specifically, the aim of the paper is to present the methodological approach which used traffic microsimulation to estimate PCEs. Focus is made on a case study which considered the conversion of a two-lane roundabout into a basic turbo roundabout with comparable size. Empirical capacity functions for both roundabouts were derived as target values to which simulated capacities by lane were compared. In order to estimate the PCEs a criterion of equivalence based on the amount of capacity used by cars and heavy vehicles is presented. AIMSUN allowed to simulate traffic conditions with different percentages of heavy vehicles at both roundabouts. Thus, variation of traffic conditions where mixed fleets operate was explored. A comparison was made between the PCEs estimated for each entry lane characterized by similar mechanism of entry maneuver. The results indicated there is a need to distinguish the impact of heavy vehicles when operational performance of a two-lane roundabout or a turbo-roundabout should be examined. Especially when circulating flows increase, a higher PCE value is expected than the value that the Highway Capacity Manual proposes for roundabouts